Microbial electrochemical fluidized bed reactor (ME-FBR): An energy-efficient advanced solution for treating real brewery wastewater with different initial organic loading rates. Issue 6 (December 2021) - Asensio, Y.; Llorente, M.; Tejedor-Sanz, S.; Fernández-Labrador, P.; Manchon, C.; Ortiz, J.M.; Ciriza, J.F.; Monsalvo, V.; Rogalla, F.; Esteve-Núñez, A.
Abstract: Electroactive bacteria are able to evolve strategies to transfer electrons with electroconductive materials. The boundaries of using electroactive bacteria to scale up wastewater treatments indicate the necessity to evaluate some of the most critical design and operational aspects. In this context, we have explored a concept so-called microbial electrochemical fluidized bed reactor (ME-FBR) for optimizing treatment of brewery wastewater by evaluating the anode potential, from + 200 mV to + 800 mV (vs. Ag/AgCl, 3 M reference electrode), in a vast range of Organic Loading Rate (OLR;0.23 kg COD/m 3 d −1 to 23.60 kg COD/m 3 d −1 ). Furthermore, the impact of the cathode nature (stainless steel mesh and sponge) and the electroconductive bed volume was evaluated regarding the wastewater treatment capacity. This manuscript reveals a positive impact on the ME-FBR capacity for treating wastewater: COD removal (87%) and nutrient removal (66% of TN and 75% of TP). Finally, the treatment energy consumption was always under 0.4 kWh Kg CODremoved −1 which was 10-fold lower than the required energy for aerating bioreactors from conventional activated sludge or membrane reactors. Graphical Abstract: ga1 Highlights: ME-FBR showed a high brewery wastewater treatment capacity. ME-FBR required ten times less energy than anaerobic treatments in WWTP. Stainless steel sponge as cathode increases the electrical efficiency of ME-FBR. COD removal depended on the installed electroconductive bed volume. ME-FBR favored high nitrogen and phosphorous removal from real brewery wastewater.